2020
DOI: 10.21203/rs.3.rs-78203/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preclinical Modeling of Chronic Inhibition of the Parkinson’s Disease Associated Kinase LRRK2 Reveals Altered Function of the Endolysosomal System in Vivo

Abstract: BackgroundThe most common mutation in the Leucine-rich repeat kinase 2 gene (LRRK2), G2019S, causes familial Parkinson’s Disease (PD) and renders the encoded protein kinase hyperactive. To date, the molecular effects of chronic LRRK2 inhibition have not yet been examined in vivo. MethodsWe evaluated the utility of newly available phospho-antibodies for Rab substrates pT73 Rab10, pS106 Rab12, pT71 Rab29 and LRRK2 autophosphorylation to examine the pharmacodynamic response to acute treatment paradigms with the p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…However, levels of pRab10 seemed unchanged (Figure 4A,B) with variability among animals (see also Ianotta et al, 2020). Previous studies have also noted that MLi-2 administration does not markedly reduce pRab10 levels in brain (Kelly et al, 2018;Kalogeropulou et al, 2020;Nirujogi et al, 2021;Kluss et al, 2021). Note that analysis of whole brain in this experiment will not capture the precise status of pRab10 levels in rare cholinergic neurons of the dorsal striatum that show LRRK2 mutation-associated ciliary deficits.…”
Section: Mli-2 Treatment Failed To Reverse Cilia Loss In Young R1441c Lrrk2 Ki Micementioning
confidence: 82%
“…However, levels of pRab10 seemed unchanged (Figure 4A,B) with variability among animals (see also Ianotta et al, 2020). Previous studies have also noted that MLi-2 administration does not markedly reduce pRab10 levels in brain (Kelly et al, 2018;Kalogeropulou et al, 2020;Nirujogi et al, 2021;Kluss et al, 2021). Note that analysis of whole brain in this experiment will not capture the precise status of pRab10 levels in rare cholinergic neurons of the dorsal striatum that show LRRK2 mutation-associated ciliary deficits.…”
Section: Mli-2 Treatment Failed To Reverse Cilia Loss In Young R1441c Lrrk2 Ki Micementioning
confidence: 82%
“…This residue, considered constitutive, is required for LRRK2 kinase activity but is not an autophosphorylation site and its phosphorylation level does not correlate with LRRK2 kinase enzymatic activity levels [49]; however, S935 is dephosphorylated when LRRK2 is inactivated, and it is widely accepted as indicative of effective LRRK2 kinase inhibition [50]. In mice injected with the highly selective LRRK2 kinase inhibitor MLi-2 [27,41,49,50], pLRRK2 was significantly reduced after 2 h (~ 90%) in all genotypes, relative to vehicle injected controls (Fig. 1C.i-ii; 2-way ANOVA treatment p < 0.0001; Uncorrected Fisher's LSD WT-WTMLi2 ****p < 0.0001; Het-HetMLi2 ***p < 0.0002; Ho-HoMLi2 ****p < 0.0001) demonstrating successful target engagement.…”
Section: S1bi-iv)mentioning
confidence: 96%
“…A recent study in nonhuman primates examined the pulmonary effects of three structurally distinct LRRK2 kinase inhibitors and found only mild histopathological lung changes that were reversable and without noticeable effect on lung function [96]. Studies in mice and rats also yielded reassuring results [38,[97][98][99]. Importantly, two recent genetic studies demonstrated that LRRK2 loss-of-function variants in humans do not appear to have negative effects on health or survival [100,101], which further argues in favor of the potential safety of LRRK2-targeted therapeutic approaches.…”
Section: Lrrk2: Therapeutic Strategiesmentioning
confidence: 97%
“…These phosphorylation sites are currently considered biomarkers for on-target Type I LRRK2 kinase inhibitors, because these inhibitors result in dephosphorylation of Ser910 and Ser935 [35]. This has been validated by several independent groups using kinase inhibitors [21,[36][37][38][39]. Additionally, using overexpression systems and purified LRRK2 phosphopeptides, more recent data have suggested that LRRK2 binding to 14-3-3 proteins also occurs in the ROC-COR GTPase domain at pSer1444 [40,41].…”
Section: Lrrk2: Substrates and Kinase Regulationmentioning
confidence: 99%